Involvement of SPARC and MMP-3 in the pathogenesis of human pterygium - Seet, Li-Fong (2013)
Purpose. To investigate the expression of SPARC and matrix metalloproteinases (MMPs) in normal conjunctiva and pterygium tissues. Methods. This study involved paired control or uninvolved conjunctiva and pterygium tissue from 21 patients. Quantitative real-time PCR was performed to assess SPARC and MMP mRNA expression, whereas Western blot analysis was performed to assess SPARC protein levels in normal conjunctiva and pterygium tissue. Tissue localization of SPARC, extracellular matrix proteins, and MMPs were determined by immunofluorescence analyses. Results. SPARC transcript and protein levels were upregulated in pterygium compared with normal conjunctiva. Immunofluorescence analyses showed localization of SPARC to the epithelial basement membrane and stroma of normal conjunctiva tissue. Increased SPARC in the pterygium stroma colocalized partially with elevated collagen I, fibronectin, α-SMA, and MMP-3. SPARC and MMP-3 also colocalized in the pterygium epithelium. Conclusions. SPARC was upregulated in pterygium and may collaborate with increased MMP-3 in some patients to account for many of the phenotypic properties characteristic of pterygium.